Adenosine levels in serum and adenosine deaminase activity in blood cells of dogs infected by rangelia vitalii - Da Silva A.S.* (2013)
Ecto-adenosinedeaminase (E-ADA) plays an important role in the production and differentiation of blood cells as well as in the control of extracellular adenosine levels. Infectious diseases can influence the synthesis of new cells or cause cell destruction, as occurs in canine rangeliosis, which results in anemia, thrombocytopenia, leukocytosis, and/or leukopenia. Thus, this study aimed to evaluate E-ADA activity in sera, erythrocytes, lymphocytes, and adenosine levels in sera samples of dogs infected by Rangelia vitalii. Twelve animals were divided into 2 groups: noninfected (n = 5) and infected by R. vitalii (n = 7). Animals were infected with 2 ml of blood containing the parasite, and parasitemia was estimated daily for 20 days by microscopic examination of peripheral blood smears. Blood collection was performed on days 0, 10, and 20 post-infection (PI) in order to evaluate the evolution of the disease. The blood collected was used to assess the activity of E-ADA. We observed an increase of E-ADA activity in sera (day 20 PI) and erythrocytes (days 10 and 20 PI) in the infected group (P < 0.05). E-ADA activity in lymphocytes was decreased on day 10, when the parasitemia was high, and increased after 20 days, when the number of circulating parasites was low. HPLC measured adenosine levels in the serum and found a reduction on days 10 and 20 PI. In conclusion, our results showed that E-ADA activity was altered in sera, lymphocytes, and erythrocytes of dogs experimentally infected by R. vitalii as well as the serum concentration of adenosine. These alterations may contribute to the pathogenesis of anemia and immune response in infected dogs. © 2013 American Society of Parasitologists.